2023
DOI: 10.1002/ijgo.14671
|View full text |Cite
|
Sign up to set email alerts
|

Use of intraoperative ultrasound to improve tension‐free vaginal tape‐obturator placement: A pilot study

Abstract: Objective To evaluate the use of intraoperative ultrasound (IUS) to achieve a postoperative optimal placement of the tension‐free vaginal tape‐obturator (TVT‐O). Methods A cohort study was performed among women who underwent TVT‐O placement. In 25 women, ultrasound was used for the placement, and based on current evidence, the optimal intraoperative and postoperative ultrasound pattern was selected. They were compared with 25 women where IUS was not used. Results IUS increased operative time (by 7.5 min), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Besides, ultrasonography may also be used intraoperatively to optimize sling position; indeed, 1 recent study has reported that the use of intraoperative ultrasonography for the placement of the MUS allows one to position the sling optimally and avoid erroneous placements. 32 However, further studies are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, ultrasonography may also be used intraoperatively to optimize sling position; indeed, 1 recent study has reported that the use of intraoperative ultrasonography for the placement of the MUS allows one to position the sling optimally and avoid erroneous placements. 32 However, further studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of our study, ultrasonographic evaluation of the MUS location seemed to be an important diagnostic tool, which may be considered in the clinical evaluation of women who were not satisfied after MUS surgery. Besides, ultrasonography may also be used intraoperatively to optimize sling position; indeed, 1 recent study has reported that the use of intraoperative ultrasonography for the placement of the MUS allows one to position the sling optimally and avoid erroneous placements 32 . However, further studies are needed.…”
Section: Discussionmentioning
confidence: 99%